High-performance hydrogen fuel cell sealing silicone rubber material and preparation method thereof

By using platinum-based catalysts and acid-resistant fillers in hydrogen fuel cell sealants, the problem of corrosion and aging of sealants in harsh environments is solved, and efficient acid resistance and stability are achieved, which extends the stack Service life.

CN119177022APending Publication Date: 2024-12-24X-POWER MATERIAL TECH (DALIAN) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410900159.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing hydrogen fuel cell sealants are difficult to operate safely for a long time in harsh environments, and face problems of strong corrosion, fatigue and aging, which affects the power generation efficiency and life of the stack.

Method used

Using the addition-formed liquid silicone rubber formula containing platinum-based catalyst, combined with polymethylhydrogen-siloxane crosslinking agent, vinyl fluorosilicone oil, white carbon black, acid-resistant filler and fluorosilane coupling agent to modify nanoparticles, and through vulcanization treatment Form a high elastic silicone rubber to enhance its acid resistance and high and low temperature properties.

Benefits of technology

It significantly improves the acid resistance and stability of sealed silicone rubber, ensures long-term operation in high-pressure, acidic and high-temperature environments, and extends the service life of hydrogen fuel cell stacks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004930261080000071
    Figure BDA0004930261080000071
Patent Text Reader

Abstract

The invention provides a high-performance hydrogen fuel cell sealing silicone rubber material and a preparation method thereof, and belongs to the field of rubber composite materials. The sealing silicone rubber material comprises a component A, a component B and a component C, wherein the component A is 45-50 parts of addition type liquid silicone rubber containing 0.01-0.2 part of a platinum-based catalyst; the component B is prepared from 45 to 50 parts of addition type liquid silicone rubber containing 0.01 to 0.5 part of a polymethylhydrosiloxane cross-linking agent; 15 to 20 parts of vinyl fluorosilicone oil; 5-10 parts of white carbon black; 5-10 parts of an acid-resistant filler; and 1-2 parts of a structure control agent. The preparation method comprises the following steps: firstly, preparing an acid-resistant filler composed of fluorosilane coupling agent modified nanoparticles and polytetrafluoroethylene micropowder; and preparing the sealing silicone rubber material. The silicone rubber composite formula provided by the invention can prevent the silicone rubber from being structured and inhibit the corrosion of an acid solution to a silicone rubber matrix; fluorine atoms are introduced into an addition type liquid silicone rubber matrix, so that the problem of poor acid resistance of sealing silicone rubber is fundamentally solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of rubber composite materials, and in particular relates to a high-performance hydrogen fuel cell sealing silicone rubber material and a preparation method thereof. Background Art

[0002] A fuel cell (FC) is a power generation device that converts the chemical energy in the fuel directly into electrical energy through an electrochemical reaction. In theory, it only needs to continuously input fuel into its cathode and anode, and electrical energy can be continuously output without the limitation of the Carnot cycle. The energy conversion efficiency is much higher than that of an internal combustion engine, and the only products are heat and water. The working noise is low, and it is a clean and environmentally friendly power generation device. Therefore, it has broad application prospects in various fields. At present, the important factors restricting the commercial development of hydrogen fuel cells are the cost and life of fuel cells. The sealing material in the fuel cell stack isolates the reaction gas air, hydrogen and coolant. As a key component to ensure the long-term stable operation of the hydrogen fuel cell, although it does not participate in the electrochemical reaction, the performance directly affects the power generation efficiency and service life of the fuel cell stack.

[0003] The working environment of these sealants is very harsh, for example: 12.5ppmH2SO4+1.8ppmHF acid electrolyte (containing H + 、SO4 2- 、F - ), high and low temperature environment (-40℃~100℃) and large stress (~1MPa). Under the above working environment, long-term use of sealant will face problems such as strong corrosion, fatigue, accelerated aging, etc., which will cause failure of stack sealing.

[0004] At present, the sealants for fuel cell stacks are mainly imported and these imported sealants cannot meet the long-life safe operation requirements of fuel cell stacks in harsh environments. It is urgent to develop a high-performance fuel cell sealant material that can meet the requirements for long-term safe operation under harsh working conditions. Summary of the invention

[0005] To solve the above problems, the present invention provides a high-performance hydrogen fuel cell sealing silicone rubber material and a preparation method thereof, so that the silicone rubber has excellent acid resistance while ensuring high and low temperature resistance, ensuring that the fuel cell stack can operate safely for a long time under harsh working conditions.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] The present invention provides a high-performance hydrogen fuel cell sealing silicone rubber material, wherein the sealing silicone rubber material comprises the following components in parts by mass:

[0008] Component A is 45-50 parts of addition-type liquid silicone rubber containing 0.01-0.2 parts of platinum-based catalyst;

[0009] Component B is 45-50 parts of addition-type liquid silicone rubber containing 0.01-0.5 parts of polymethyl hydrogen siloxane crosslinking agent;

[0010] 15-20 parts of vinyl fluorosilicone oil;

[0011] 5-10 parts of white carbon black;

[0012] 5-10 parts of acid-resistant filler;

[0013] 1 to 2 parts of structure control agent.

[0014] Specific:

[0015] The addition type liquid silicone rubber is methyl vinyl silicone rubber, the viscosity of component A is 40000-60000 mPa·s (23°C, D=25 / s), and the viscosity of component B is 20000-30000 mPa·s (23°C, D=25 / s).

[0016] The vinyl fluorosilicone oil is one or more of vinyl-terminated polymethyltrifluoropropylsiloxane and vinyl (trifluoromethyl) dimethylsilane, and has a viscosity of 10000-40000 cps.

[0017] The acid-resistant filler comprises 2 to 10 parts of polytetrafluoroethylene powder and 2 to 10 parts of fluorosilane coupling agent modified nanoparticles.

[0018] Furthermore, the fluorosilane coupling agent modified nanoparticles are obtained by modifying nanoparticles with a fluorosilane coupling agent, specifically: the fluorosilane coupling agent is one or more of alkoxyfluorosilanes (such as tridecafluorooctyl triethoxysilane, etc.), vinylfluorosilanes (such as vinyl dimethylfluorosilane, etc.), and aminofluorosilanes (such as 3-aminopropyl dimethylfluorosilane, etc.). The nanoparticles are one or more of nano barium sulfate, nano talc, and nano mica powder. The size of the polytetrafluoroethylene powder is ≤1μm, and the size of the nano barium sulfate, nano talc, and nano mica powder is 100-200nm.

[0019] The white carbon black is fumed white carbon black, and the primary particle size is 7 to 40 nm.

[0020] The structure control agent is hydroxy silicone oil, and the mass fraction of hydroxyl group is 6-10%.

[0021] Another object of the present invention is to provide a method for preparing a high-performance hydrogen fuel cell sealing silicone rubber material, the specific steps comprising:

[0022] The first step is to prepare an acid-resistant filler composed of fluorosilane coupling agent modified nanoparticles and polytetrafluoroethylene micropowder, as follows:

[0023] 1.1) Mix the nanoparticles and anhydrous ethanol in a mass ratio of 1:10 to 1:16 to prepare a suspension, and disperse by ultrasonic at room temperature for 30 to 40 minutes;

[0024] 1.2) Adding a fluorosilane coupling agent to the suspension prepared in step 1.1), stirring at a speed of 300-400 r / min, and reacting at 80-85° C. for 5-6 hours; the mass ratio of the fluorosilane coupling agent to the nanoparticles is 1:2.

[0025] 1.3) After the suspension is cooled, centrifuge at 4000-5000 r / min for 10-15 min, wash with anhydrous ethanol for multiple times and then dry to obtain fluorosilane coupling agent modified nanoparticles; the drying temperature is 85-100° C. and the drying time is 20-24 h.

[0026] 1.4) The fluorosilane coupling agent modified nanoparticles obtained in step 1.3) are uniformly mixed with polytetrafluoroethylene powder in a ratio of 3:5 to 1:1 to serve as an acid-resistant filler.

[0027] The second step is to prepare the sealing silicone rubber material, as follows:

[0028] 2.1) Weigh the addition type liquid silicone rubber of component A and the addition type liquid silicone rubber of component B according to the raw material ratio;

[0029] 2.2) Weigh half of the raw material ratio of white carbon black, acid-resistant filler, and structure control agent, weigh vinyl fluorosilicone oil in proportion, add the above raw materials in small amounts and multiple times to the A component addition type liquid silicone rubber obtained in step 2.1), and stir at 300-350 r / min to obtain A component composite silicone rubber; the stirring time is 25-30 min; in this step, the hydroxyl groups bound to the surface of white carbon black and the oxygen atoms of the methyl vinyl silicone rubber are hydrogen bonded, or the particles and the matrix interact with each other by physical adsorption force, thereby increasing the physical crosslinking points of the system; the acid-resistant filler is distributed in the silicone rubber, inhibiting the corrosion of the silicone rubber by the acid solution; the structure control agent prevents the silicone rubber from being structured and hardened; the vinyl fluorosilicone oil can be grafted to the silicone rubber under the action of a platinum-based catalyst to improve the stability of the silicone rubber.

[0030] 2.3) Weigh half of the raw material ratio of white carbon black, acid-resistant filler, and structure control agent, add the above raw materials in small amounts and multiple times to the B component addition type liquid silicone rubber obtained in step 2.1), accompanied by stirring at 300-350r / min, to obtain the B component composite silicone rubber. The stirring time is 25-30min; in this step, the hydroxyl groups bound to the surface of white carbon black and the oxygen atoms of the methyl vinyl silicone rubber are hydrogen bonded, or the particles and the matrix interact with each other by physical adsorption, increasing the physical crosslinking points of the system; the acid-resistant filler is distributed in the silicone rubber, inhibiting the acid solution from corroding the silicone rubber, and the structure control agent prevents the silicone rubber from being structured and hardened.

[0031] 2.4) stirring and mixing the composite silicone rubber of group A obtained in 2.2) and the composite silicone rubber of component B obtained in 2.3) at a rotation speed of 300 to 350 r / min to obtain composite silicone rubber C; in this step, the composite silicone rubber of component A and the composite silicone rubber of component B undergo a silylation reaction with a crosslinking agent, polymethylhydrogensiloxane, under the action of a platinum-based catalyst to form composite silicone rubber C.

[0032] 2.5) vacuum degassing the composite silicone rubber C obtained in step 2.4) to obtain liquid silicone rubber, with a vacuum degree of -0.2 to -0.1 MPa, a temperature of 23 to 25° C., and a time of 25 to 30 min;

[0033] 2.6) The liquid silicone rubber obtained in step 2.5) is vulcanized at a vulcanization temperature of 160-165°C, a pressure of 8-10 MPa, a vulcanization time of 8-10 min, and then cooled to room temperature naturally and placed for 8-16 hours. In this step, the liquid silicone rubber further undergoes a cross-linking reaction at a given temperature and pressure to form a highly elastic silicone rubber.

[0034] Beneficial effects of the present invention:

[0035] (1) The present invention designs a suitable silicone rubber composite formula, white carbon black can enhance the cross-linked network of silicone rubber, and the structure control agent ensures the dispersibility of white carbon black and prevents the silicone rubber from structuring. + ) and fluoride ion (F - ), which will damage the silicone rubber matrix.

[0036] (2) In the acid-resistant filler polytetrafluoroethylene micropowder selected by the present invention, the F atom has strong electronegativity and low polarizability, and the formed CF bond forms a barrier protection effect on the surrounding chemical bonds, thereby inhibiting the corrosion of the silicone rubber matrix by the acidic solution; the nanoparticles, after being modified by a fluorosilane coupling agent, are grafted with low surface energy fluorine-containing functional groups on the surface. While improving the dispersibility, the spatial barrier protection of the fluorine-containing functional groups enhances the resistance of the nanoparticles to acidic solutions, thereby further improving the acid resistance of the sealing silicone rubber; through vinyl fluorosilicone oil, fluorine atoms are introduced into the addition-type liquid silicone rubber collectively, fundamentally improving the poor acid resistance of the sealing silicone rubber. DETAILED DESCRIPTION

[0037] In order to better understand the present invention, the present invention is further described below by way of examples. The examples are only used to explain the present invention and will not constitute any limitation to the present invention.

[0038] Example 1

[0039] The hydrogen fuel cell sealing silicone rubber is composed of the following raw materials in parts by mass: 45 parts of addition-type liquid silicone rubber of component A, 45 parts of addition-type liquid silicone rubber of component B, 15 parts of vinyl-terminated polymethyltrifluoropropylsiloxane, 5 parts of fumed silica, 2.5 parts of polytetrafluoroethylene micropowder, 2.5 parts of tridecafluorooctyltriethoxysilane-modified nano-barium sulfate, and 1 part of hydroxy silicone oil.

[0040] (1) The preparation method of tridecafluorooctyl triethoxysilane modified nano barium sulfate comprises the following steps:

[0041] 1.1) Prepare a suspension with a mass ratio of nano-barium sulfate to anhydrous ethanol = 1:10, and perform ultrasonic dispersion at room temperature for 30 minutes;

[0042] 1.2) Weigh tridecafluorooctyl triethoxysilane in a mass ratio of tridecafluorooctyl triethoxysilane to nano-barium sulfate = 1:2, add tridecafluorooctyl triethoxysilane to the suspension prepared in step 1.1), stir at a speed of 300 r / min, and react at 80°C for 5 h;

[0043] 1.3) After the suspension is cooled, centrifuge at 4000r / min for 10min and wash three times with anhydrous ethanol;

[0044] 1.4) Dry in a drying oven at 85°C for 24 hours.

[0045] (2) Preparing hydrogen fuel cell sealing silicone rubber according to the above formula includes the following steps:

[0046] 2.1) Weigh 45 parts of component A addition type liquid silicone rubber and 45 parts of component B addition type liquid silicone rubber according to the raw material ratio;

[0047] 2.2) According to half of the raw material ratio, 2.5 parts of fumed silica, 1.25 parts of polytetrafluoroethylene powder, 1.25 parts of tridecafluorooctyl triethoxysilane-modified nano-barium sulfate, and 0.5 parts of hydroxy silicone oil are weighed, and 15 parts of vinyl-terminated polymethyl trifluoropropyl siloxane are weighed in proportion, and added in small amounts and multiple times to the A component addition-type liquid silicone rubber obtained in step 2.1), accompanied by stirring at 300 r / min to obtain the A component composite silicone rubber; according to half of the raw material ratio, 2.5 parts of fumed silica, 1.25 parts of polytetrafluoroethylene powder, 1.25 parts of tridecafluorooctyl triethoxysilane-modified nano-barium sulfate, and 0.5 parts of hydroxy silicone oil are weighed, and added in small amounts and multiple times to the B component addition-type liquid silicone rubber obtained in step 2.1), accompanied by stirring at 300 r / min to obtain the B component composite silicone rubber. The composite silicone rubber of group A and the composite silicone rubber of group B are stirred and mixed uniformly at a rotation speed of 300 r / min to obtain a composite silicone rubber;

[0048] 2.3) vacuum degassing the composite silicone rubber obtained in step 2.2) at a vacuum degree of -0.1 MPa, a temperature of 23° C., and a time of 25 min;

[0049] 2.4) The composite silicone rubber obtained in step 2.3) was vulcanized at a vulcanization temperature of 160° C., a pressure of 8 MPa, a vulcanization time of 8 min, and then naturally cooled to room temperature and placed for 16 h to obtain a sample.

[0050] The sample has a glossy surface and uniform texture, and the filler is well dispersed in the silicone rubber. The compression set test conditions are: 95°C, 25% compression set, and aging for 1008h in 12.5ppmH2SO4+1.8ppmHF solution. Under this condition, the permanent compression set of Example 1 is ≤10.05%, and the performance is good, which can ensure the high-efficiency and long-term operation of the hydrogen fuel cell.

[0051] Example 2

[0052] The hydrogen fuel cell sealing silicone rubber is composed of the following raw materials in parts by mass: 50 parts of addition-type liquid silicone rubber of component A, 50 parts of addition-type liquid silicone rubber of component B, 20 parts of vinyl (trifluoromethyl) dimethyl silane, 10 parts of fumed silica, 5 parts of polytetrafluoroethylene micropowder, 5 parts of vinyl dimethyl fluorosilane-modified nano talc, and 2 parts of hydroxy silicone oil.

[0053] (1) The preparation method of vinyldimethylfluorosilane modified nano talc powder comprises the following steps:

[0054] 1.1) Prepare a suspension according to the mass ratio of nano-talc powder to anhydrous ethanol = 1:16, and ultrasonically disperse at room temperature for 40 minutes;

[0055] 1.2) Weigh vinyldimethylfluorosilane in a mass ratio of vinyldimethylfluorosilane to nano-talc powder = 1:2, add it to the suspension prepared in step 1.1), stir at a speed of 400 r / min, and react at 85°C for 6 hours;

[0056] 1.3) After the suspension is cooled, centrifuge at 5000r / min for 15min and wash three times with anhydrous ethanol;

[0057] 1.4) Dry in a drying oven at 85°C for 24 hours.

[0058] (2) Preparing hydrogen fuel cell sealing silicone rubber according to the above formula includes the following steps:

[0059] 2.1) Weigh 50 parts of component A addition type liquid silicone rubber and 50 parts of component B addition type liquid silicone rubber according to the raw material ratio;

[0060] 2.2) According to half of the raw material ratio, 5 parts of fumed silica, 2.5 parts of polytetrafluoroethylene powder, 2.5 parts of vinyl dimethyl fluorosilane modified nano talc, and 1 part of hydroxy silicone oil are weighed, and 20 parts of vinyl (trifluoromethyl) dimethyl silane are weighed in proportion, and added to the A component addition type liquid silicone rubber obtained in step 2.1) in small amounts and multiple times, accompanied by stirring at 350r / min to obtain the A component composite silicone rubber; according to half of the raw material ratio, 5 parts of fumed silica, 2.5 parts of polytetrafluoroethylene powder, 2.5 parts of vinyl dimethyl fluorosilane modified nano barium sulfate, and 1 part of hydroxy silicone oil are weighed, and added to the B component addition type liquid silicone rubber obtained in step 2.1) in small amounts and multiple times, accompanied by stirring at 350r / min to obtain the B component composite silicone rubber. The A component composite silicone rubber and the B component composite silicone rubber are stirred and mixed evenly at a speed of 350r / min to obtain the composite silicone rubber;

[0061] 2.3) vacuum degassing the composite silicone rubber obtained in step 2.2) at a vacuum degree of -0.2 MPa, a temperature of 25° C., and a time of 30 min;

[0062] 2.4) The composite silicone rubber obtained in step 2.3) was vulcanized at a vulcanization temperature of 165° C., a pressure of 10 MPa, a vulcanization time of 10 min, and then naturally cooled to room temperature and placed for 16 h.

[0063] Example 3

[0064] The hydrogen fuel cell sealing silicone rubber is composed of the following raw materials in parts by mass: 48 parts of addition-type liquid silicone rubber of component A, 48 parts of addition-type liquid silicone rubber of component B, 18 parts of vinyl-terminated polymethyltrifluoropropylsiloxane, 8 parts of fumed silica, 5 parts of polytetrafluoroethylene micropowder, 3 parts of 3-aminopropyldimethylfluorosilane-modified nano-mica powder, and 1.5 parts of hydroxy silicone oil.

[0065] (1) The preparation method of 1.3-aminopropyldimethylfluorosilane modified nano mica powder comprises the following steps:

[0066] 1.1) Prepare a suspension according to the mass ratio of nano-mica powder to anhydrous ethanol = 1:14, and ultrasonically disperse at room temperature for 35 minutes;

[0067] 1.2) Weigh 3-aminopropyldimethylfluorosilane in a mass ratio of 3-aminopropyldimethylfluorosilane to nano-mica powder = 1:2, add it to the suspension prepared in step 1.1), stir at a speed of 350 r / min, and react at 83° C. for 5.5 h;

[0068] 1.3) After the suspension is cooled, centrifuge at 4500r / min for 13min and wash three times with anhydrous ethanol;

[0069] 1.4) Dry in a drying oven at 100°C for 24 hours.

[0070] (2) Preparing hydrogen fuel cell sealing silicone rubber according to the above formula includes the following steps:

[0071] 2.1) Weigh 48 parts of component A addition type liquid silicone rubber and 48 parts of component B addition type liquid silicone rubber according to the raw material ratio;

[0072] 2.2) According to half of the raw material ratio, 4 parts of fumed silica, 2.5 parts of polytetrafluoroethylene powder, 1.5 parts of 3-aminopropyldimethylfluorosilane modified nano mica powder, and 0.75 parts of hydroxy silicone oil are weighed, and 18 parts of vinyl-terminated polymethyltrifluoropropylsiloxane are weighed in proportion, and added to the A component addition type liquid silicone rubber obtained in step 2.1) in small amounts and multiple times, accompanied by stirring at 330r / min to obtain the A component composite silicone rubber; according to half of the raw material ratio, 4 parts of fumed silica, 2.5 parts of polytetrafluoroethylene powder, 1.5 parts of 3-aminopropyldimethylfluorosilane modified nano mica powder, and 0.75 parts of hydroxy silicone oil are weighed, and added to the B component addition type liquid silicone rubber obtained in step 2.1) in small amounts and multiple times, accompanied by stirring at 330r / min to obtain the B component composite silicone rubber. The A component composite silicone rubber and the B component composite silicone rubber are stirred and mixed evenly at a speed of 330r / min to obtain the composite silicone rubber;

[0073] 2.3) vacuum degassing the composite silicone rubber obtained in step 2.2) at a vacuum degree of -0.15 MPa, a temperature of 24° C., and a time of 27 min;

[0074] 2.4) The composite silicone rubber obtained in step 2.3) was vulcanized at a vulcanization temperature of 163° C., a pressure of 9 MPa, a vulcanization time of 9 min, and then naturally cooled to room temperature and placed for 16 h.

[0075] Comparative Example 1

[0076] The difference from Example 3 is that no acid-resistant filler is added, and the other components and processes remain unchanged. The prepared hydrogen fuel cell sealing silicone rubber is subjected to performance testing in the same manner as Example 3.

[0077] According to the test method (Shore A hardness test refers to GB / T 531.1; tensile test refers to GB / T 528-2009; permanent compression set test refers to GB / T 7759)

[0078] Table 1. Performance parameters of Examples 1, 2, 3 and Comparative Examples

[0079]

[0080]

[0081] From the data analysis in Table 1, it can be seen that after adding the acid-resistant filler, that is, under the synergistic effect of polytetrafluoroethylene micropowder and fluorosilane coupling agent modified nanoparticles, the performance of hydrogen fuel cell sealing silicone rubber is significantly improved. Compared with comparative example 1, the tensile strength is increased by 0.97MPa, the elongation at break is increased by 87.39%, the compression permanent deformation at 95℃, 25%, 24h is reduced by 2.59%, and the compression permanent deformation at 95℃, 25%, after aging for 1008h in RS solution is reduced by 8.07%.

[0082] Anything not mentioned above is applicable to the prior art.

Claims

1. A high-performance hydrogen fuel cell sealing silicone rubber material, characterized in that: The sealing silicone rubber material comprises the following components in parts by mass: Component A is 45-50 parts of addition-type liquid silicone rubber containing 0.01-0.2 parts of platinum-based catalyst; Component B is 45-50 parts of addition-type liquid silicone rubber containing 0.01-0.5 parts of polymethyl hydrogen siloxane crosslinking agent; 15-20 parts of vinyl fluorosilicone oil; 5-10 parts of white carbon black; 5-10 parts of acid-resistant filler; 1 to 2 parts of structure control agent.

2. A high performance hydrogen fuel cell sealing silicone rubber material according to claim 1, characterized in that: The addition type liquid silicone rubber is methyl vinyl silicone rubber, the viscosity of component A is 40000-60000 mPa·s, and the viscosity of component B is 20000-30000 mPa·s.

3. A high performance hydrogen fuel cell sealing silicone rubber material according to claim 1, characterized in that: The vinyl fluorosilicone oil is one or more of vinyl-terminated polymethyltrifluoropropylsiloxane and vinyl (trifluoromethyl) dimethylsilane.

4. A high performance hydrogen fuel cell sealing silicone rubber material according to claim 1, characterized in that: The acid-resistant filler comprises 2-10 parts of polytetrafluoroethylene powder and 2-10 parts of fluorosilane coupling agent modified nanoparticles, wherein the fluorosilane coupling agent modified nanoparticles are obtained by modifying nanoparticles with a fluorosilane coupling agent.

5. A high performance hydrogen fuel cell sealing silicone rubber material according to claim 4, characterized in that: The fluorosilane coupling agent is one or more of alkoxyfluorosilanes, vinylfluorosilanes, and aminofluorosilanes; the nanoparticles are one or more of nano-barium sulfate, nano-talc powder, and nano-mica powder.

6. The high-performance hydrogen fuel cell sealing silicone rubber material according to claim 1, characterized in that: The white carbon black is fumed white carbon black with a primary particle size of 7 to 40 nm; the structure control agent is hydroxy silicone oil with a hydroxyl mass fraction of 6 to 10%.

7. A method for preparing a high-performance hydrogen fuel cell sealing silicone rubber material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The first step is to prepare an acid-resistant filler composed of fluorosilane coupling agent modified nanoparticles and polytetrafluoroethylene micropowder: 1.1) Mix the nanoparticles and anhydrous ethanol to prepare a suspension, and disperse them by ultrasonication; 1.2) Add the fluorosilane coupling agent to the suspension and react at 80-85°C for 5-6 hours; 1.3) After the suspension is cooled, centrifuged, washed and then dried to obtain fluorosilane coupling agent modified nanoparticles; 1.4) The fluorosilane coupling agent modified nanoparticles obtained in step 1.3) are uniformly mixed with polytetrafluoroethylene powder in proportion to serve as an acid-resistant filler. The second step is to prepare the sealing silicone rubber material, as follows: 2.1) Weigh the addition type liquid silicone rubber of component A and the addition type liquid silicone rubber of component B according to the raw material ratio; 2.2) weighing white carbon black, acid-resistant filler, and structure control agent according to half of the raw material ratio, weighing vinyl fluorosilicone oil according to the ratio, adding the above raw materials in small amounts and multiple times to the A component addition type liquid silicone rubber obtained in step 2.1), while stirring, to obtain A component composite silicone rubber; 2.3) Weighing white carbon black, acid-resistant filler, and structure control agent according to half of the raw material ratio, adding the above raw materials in small amounts and multiple times to the B component addition type liquid silicone rubber obtained in step 2.1), while stirring, to obtain the B component composite silicone rubber; 2.4) stirring and mixing the composite silicone rubber of group A obtained in 2.2) and the composite silicone rubber of group B obtained in 2.3) to obtain composite silicone rubber C; 2.5) vacuum degassing the composite silicone rubber C obtained in 2.4) to obtain liquid silicone rubber; 2.6) The liquid silicone rubber obtained in 2.5) is vulcanized and then left to stand for a certain period of time to obtain a highly elastic silicone rubber.

8. The method for preparing a high-performance hydrogen fuel cell sealing silicone rubber material according to claim 7, characterized in that: In the above 1.1), the mass ratio of nanoparticles to anhydrous ethanol is 1:10 to 1:16, and ultrasonic dispersion is performed for 30 to 40 minutes; In the above 1.2), the mass ratio of the fluorosilane coupling agent to the nanoparticles is 1:2; In 1.3), the rotation speed and time of the centrifugal treatment are 4000-5000 r / min and 10-15 min respectively; the drying temperature is 85-100° C. and the time is 20-24 h; In the above 1.4), the ratio of the fluorosilane coupling agent modified nanoparticles to the polytetrafluoroethylene powder is 3:5 to 1:

1.

9. The method for preparing a high-performance hydrogen fuel cell sealing silicone rubber material according to claim 7, characterized in that: In the above 2.2), the stirring time is 25 to 30 minutes, and the stirring speed is 300 to 350 r / min; In the above 2.3), the stirring time is 25 to 30 minutes, and the stirring speed is 300 to 350 r / min; In the above 2.3), the stirring speed is 300-350 r / min; In the above 2.5), the vacuum degree is -0.2 to -0.1 MPa, the temperature is 23 to 25°C, and the time is 25 to 30 minutes. In the above 2.6), the vulcanization temperature is 160-165° C., the pressure is 8-10 MPa, the vulcanization time is 8-10 min, and the mixture is left to stand for 8-16 h.

Citation Information

Cited By

  • Frost-crack-resistant cable and preparation method thereof

    CN120272015A

  • An anti-cracking cable and a method for manufacturing the same

    CN120272015B